A simbólica tessitura do sagrado em Clarice Lispector: paralelos entre a Bíblia e o conto "Onde estiveres de noite". - Melo, Damiana Silva de (2019)
The history of humanity is guided by narratives, among them, those widely disseminated by biblical and literary texts approached in their cultures and aligned with structures, beliefs, knowledge and symbologies. Parallel to this perspective, the research proposes a review of the analyzes elaborated by Auerbach (1972, 2007) on the course of western literature and the contribution of philology to the preservation of classical writings; passing through the models pointed out by the intellectuals of Christianity, to pass on the teachings contained in the Scriptures, culminating in the productions of the Renaissance, Romantic movements and their links with the sacred texts. Armed by the hermeneutics of Meletínki (1998) in discussing the archetypes, even contrasting Jung's studies in this regard, the paper presents the contributions of Meletínki on the literary archetypes and their functions given in the texts. In this discussion we propose the analysis of Clarice Lispector's short story Where You Were at Night (1997), starting from the possible contributions of the dialogue between Literature and Religious Sciences, in order to examine the architecture and the concert set up by Clarice Lispector by having some segments of the Bible to discuss human intimacy and its connections in the social, philosophical and spiritual spheres, that generate conflicts, but also to provide the foundations that sustain their lives. The sacred statement by Lispector reflects the richness of the encounter with transcendence, which, reported in the dream of the characters, allows the reader to delve into the depths of their desires, values and moral postures, proving that the shadow and light of the night also reside in the human being who seeks enlightenment before the divine to soften or heal the disease of power, the greatest sorrow of the terrestrial race. The exploration is articulated around two poles: the text and the interpretation of the text supported by the lens of the Sciences of Religion; in the intention to establish counterpoints when following the dynamics of the texts in their crossings; in the clear interest of following the role of hermeneutics: to verify the instance of discourses, writing, work and literary genre, and world connections of the text, preventing superficialities in order to sneak away from the misappropriation of textual productions. Sovereignty that is still installed in writings and in human relationships, which subjugates the feminine, the poor, the Jew, but these portions of society move in dreamy and real-life endures in search of the divine and find in it a force of peace and war to annihilate what was built in the names of the gods to subdue the minor and exclude him.